Demokracja, utopia, wychowanie - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
„Every discussion of democracy”, says Giovanni Sartori, „revolves around three concepts: sovereignty of the people, equality and self-government”. In these discussions, the credible linkage of this ideas and their full development, that is to say, adequate to the needs, complexity of functioning and size of a modern nation-state, it creates the image, and at the same time, the political promise of a sufficiently perfect society, that will be possible in the future through effective education. This article aims to develop an understanding of the relationship between selected democratic theories, the concept of utopia and education.
Keywords: democracy theory; education; utopia